Comparing single‐target and multitarget approaches for postoperative circulating tumour DNA detection in stage II–III colorectal cancer patients. Issue 20 (18th August 2022) - Henriksen, Tenna Vesterman; Reinert, Thomas; Rasmussen, Mads Heilskov; Demuth, Christina; Løve, Uffe Schou; Madsen, Anders Husted; Gotschalck, Kåre Andersson; Iversen, Lene Hjerrild; Andersen, Claus Lindbjerg
Abstract : Circulating tumour DNA (ctDNA) detection for postoperative risk stratification in cancer patients has great clinical potential. However, low ctDNA abundances complicates detection. Multitarget (MT) detection strategies have been developed to increase sensitivity. Yet, empirical evidence supporting performance gains of MT vs. single‐target (ST) strategies in a postoperative setting is limited. We compared ctDNA detection in 379 paired plasma samples from 112 stage II–III colorectal cancer patients by ST digital PCR and MT sequencing of 16 patient‐specific variants. The strategies exhibited good concordance (90%, Cohen's Kappa 0.79), with highly correlated ctDNA quantifications (Pearson r = 0.985). A difference was observed in ctDNA detection preoperatively (ST 72/92, MT 88/92). However, no difference was observed immediately after surgery in recurrence (ST 11/22, MT 10/22) or nonrecurrence (both 2/34) patients. In serial samples, detection was similar within recurrence (ST 13/16, MT 14/16) and nonrecurrence (ST 3/49, MT 1/49) patients. Both approaches yielded similar lead times to standard‐of‐care radiology (ST 4.0 months, MT 4.1 months). Our findings do not support significant performance gains of the MT strategy over the ST strategy for postoperative ctDNA detection. Abstract : Circulating tumour DNA (ctDNA) is potentially useful for postoperative risk stratification, but its detection is challenging. To examine whether tracking multiple targets improves detection, we analysed paired plasma samples from colorectal cancer patients by tracking one or 16 targets. We observed no difference in postoperative ctDNA detection, concluding that widely available single‐target analyses can provide equally good results for recurrence‐risk stratification.